2014
DOI: 10.1007/s12029-013-9573-8
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Non-B non-C Hepatocellular Carcinoma in Mid Delta Region, Egypt

Abstract: Pesticides and smoking heavy exposure can be considered as primary risks for non-B non-C HCC. Phosphate and ammonium sulfate fertilizers were associations. The study will increase awareness for better prevention and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This sector is at high risk for pesticides exposure and consequently high risk for developing HCC especially among rural males in addition to exposure to other risk factors (HBV and HCV) [4,6,29,30]. In mid delta region in Egypt, both pesticides and fertilizers have been suggested to be an independent risk factor for HCC [31].…”
Section: (A) Chemical Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sector is at high risk for pesticides exposure and consequently high risk for developing HCC especially among rural males in addition to exposure to other risk factors (HBV and HCV) [4,6,29,30]. In mid delta region in Egypt, both pesticides and fertilizers have been suggested to be an independent risk factor for HCC [31].…”
Section: (A) Chemical Compoundsmentioning
confidence: 99%
“…Recently, a systematic review of 81 epidemiological studies [35] showed that there is an increase in the incidence of HCC risk and mortality among cigarette smokers. In Egypt, conflicting results were found regarding the association between tobacco smoking and the overall risk of HCC [5,30,31]. There is gender variation of HCC incidence being the fifth most common cancer in men (7.5%) and the ninth in women (3.4%) [10].…”
Section: (C) Smokingmentioning
confidence: 99%
“…To supply the demand many countries, including Brazil, have adopted intensive agricultural practices, with heavy use of chemical fertilizers and an array of chemical treatments to combat pests (insecticides, pesticides, fungicides) and competing plants (herbicides), all of which have a negative impact on the environment [24]. Although coffee consumption has been linked to numerous physiological benefits [5–8], several studies have associated pesticides or herbicides in coffee agriculture to health problems [9, 10], including various types of cancer [11]. More recently, organic farming, which removes the use of chemical treatments [12], has provided a healthier alternative that benefits consumers, farmers, and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries such as Egypt, exposure to inorganic compounds like pesticides and fertilizers has been suggested to be an independent risk factor for HCC 37 . Similarly, dietary aflatoxin is a known risk factor for HCC 38…”
Section: Hcc Risk Factors Screening and Early Diagnosis In Mena Regio...mentioning
confidence: 99%
“…36 In some countries such as Egypt, exposure to inorganic compounds like pesticides and fertilizers has been suggested to be an independent risk factor for HCC. 37 Similarly, dietary aflatoxin is a known risk factor for HCC. 38 The responses obtained from the experts indicate an increasing trend in the incidence of HCC in the MENA region.…”
Section: Risk Factors Associated With Hcc In the Mena Regionmentioning
confidence: 99%